Foreign Debt, Financial Stability, Exchange Rate Volatility and Economic Growth in South Asian Countries - Ali, Amjad (Journal of Business and Economic Options, 2022)
The current study has examined the link between exchange rate volatility, financial stability, foreign debt, and economic growth in a few South Asian nations from 1985 to 2020. The findings show that labor force participation has a positive and significant link with economic growth. Financial stability has a positive and significant influence on economic growth. Physical capital has a positive and significant relationship with economic growth because South Asian countries have labor as a larger factor of production. Foreign debt has a negative and insignificant influence on the level of growth, whereas, exchange rate volatility has a positive and significant relationship with economic growth. The overall results conclude that exchange rate volatility, financial stability, foreign debt, physical capital availability, and labor force participation are playing important roles in determining economic growth in the case of selected South Asian countries.